Reengineering for Accessibility: A Strategy Based on Software Awareness - de Oliveira, Romeu Ferreira; Moura, Ana Maria da Mota; Leite, Julio Cesar Sampaio do Prado (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2018: Anais do XVII Simpósio Brasileiro de Qualidade de Software, 2018)
Almost a decade after the release of the W3C Web Content Accessibility Guidelines (WCAG) version 2.0, the low level of accessibility in web sites and web applications is still worrying. A problem that aggravates this situation involves the fact that web accessibility requirements are often addressed when the application is fully developed. Such delayed processing often results in significant rework, increasing costs with new recoding analyzes, which may be totally outside the scope and budget of the project. As we believe that the need for accessibility may vary according to the users and their context, in this article, we approach a strategy to promote web accessibility in legacy systems through the use of software awareness. In this process of reengineering, we deal with the interaction of web accessibility with another nonfunctional requirement: Software Awareness. In this way, we use self-adaptation strategies to provide customized accessibility. As a result of our strategy, we present a hybrid SIG (Softgoal Interdependency Graphs) containing the requirements of accessibility and software awareness, based on the concepts of the NFR Framework, and its application in reengineering a real system based on Android.